2022
DOI: 10.1093/cid/ciac356
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cutaneous Balamuthia mandrillaris Infection With Diminazene Aceturate: A Report of 4 Cases

Abstract: Four cases of cutaneous Balamuthia mandrillaris infection were treated with diminazene aceturate. One patient was cured with mainly monotherapy, 2 patients were cured with diminazene aceturate and excision, and 1 patient died of drug induced liver damage. This is the first report of Balamuthia mandrillaris infection treated with diminazene aceturate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For example, a 57-year-old cutaneous B. mandrillaris infected patient died with severe liver damage potentially due to complications of the diminazene aceturate treatment they received. 41 Another patient with B. mandrillaris GAE was treated for more than 2 months with the recommended multiple-drug regimen (flucytosine, pentamidine, fluconazole, sulfadiazine, azithromycin, miltefosine, and albendazole) and developed adverse effects, including acute kidney injury and myelosuppression. 35,42 These examples indicate that new treatments with lower toxicities are needed for B. mandrillaris .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a 57-year-old cutaneous B. mandrillaris infected patient died with severe liver damage potentially due to complications of the diminazene aceturate treatment they received. 41 Another patient with B. mandrillaris GAE was treated for more than 2 months with the recommended multiple-drug regimen (flucytosine, pentamidine, fluconazole, sulfadiazine, azithromycin, miltefosine, and albendazole) and developed adverse effects, including acute kidney injury and myelosuppression. 35,42 These examples indicate that new treatments with lower toxicities are needed for B. mandrillaris .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study examined the effects of the conjugation of amphotericin B on N. fowleri, revealing encouraging results; however, in this study, silver nanoparticles were utilized for the conjugation, and the cytotoxicity of the compounds alone was not evaluated [ 8 ]. Furthermore, until now, conjugated curcumin and amphotericin B have not been evaluated on B. mandrillaris , for which the number of reported cases is evident [ 45 , 46 , 47 ]. The nanocarriers utilized in this study also revealed greater drug loading efficiency, thus showing their capability for higher drug release to the desired target site [ 30 ].…”
Section: Discussionmentioning
confidence: 99%